ROMANTIC DRAMA OF KOREAN AND AUDIENCE READING: ANALYSIS OF RECEPTION - Puji Rianto (Metakom, 2019)
The research was conducted to answer how the reception or intepretation of the audience among young people towards Korean romantic drama. Romantic drama is a theme that is taken because it is sticky in human life, especially teenagers. By using qualitative methods by adopting netnography, this study found that reading of audiences can be divided into three forms, namely dominant-hegemonic, negotiating, and opposition. The dominant-hegemonic reading model is the most powerful reading model compared to other models. The dominant-hegemonic reading model is indicated by a romantic story that touches the audience's emotionality dimension. The reading of the negotiations, on the other hand, accepting romantic drama insofar as it does not involve the social class, while the reading of the opposition totally rejects Korean romantic drama as unreal.